Ultrathin high-tensile composite metal current collector

CN224907992UActive Publication Date: 2026-10-27TIANJIN YANJI NEW MATERIAL TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202522303357.3
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2025-10-30
Publication Date
2026-10-27
Estimated Expiration
2035-10-30

AI Technical Summary

Technical Problem

该专利所得的集流体无法将厚度压缩到小于10μm,拉伸强度为400-800MPa,其面临厚度与拉伸强度等性能的矛盾

Benefits of technology

[0013]与现有技术相比,本实用新型具有如下技术效果:与纯铜基集流体对比,大幅提高了拉伸强度,同时满足现有电池要求,与其他镍基或者镍铁合金集流体相比导电性更强,拉伸强度和延伸率更高,而且制备成本更低。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN224907992U_ABST
    Figure CN224907992U_ABST
Patent Text Reader

Abstract

The utility model discloses a kind of ultra-thin high tensile composite metal current collector, belong to battery material technical field.The current collector includes nickel metal layer and copper metal layer arranged at the two sides or any one side of the nickel metal layer;The nickel metal layer includes pure nickel.The preparation method includes: plating interlayer on bed layer;First copper metal layer, nickel metal layer are successively plated on the interlayer;Or, first copper metal layer, nickel metal layer, second copper metal layer are successively plated on the interlayer;The interlayer and the first copper metal layer are separated, namely obtained.The utility model is prepared by the preparation process route of bed layer, interlayer and current collector functional layer and the formula design to plating solution, realize the ultra-thin of composite current collector, and compared with other current collector of same thickness level, the tensile strength is greatly improved, which is far beyond expectation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This utility model belongs to the field of battery material technology, and in particular relates to an ultra-thin high tensile strength composite metal current collector. Background Technology

[0002] In the development of lithium batteries, the current collector, as a key component that carries active materials and conducts current, directly affects the overall performance of the battery. Traditional current collector materials, such as copper foil and aluminum foil, have gradually revealed many limitations in the face of the ever-increasing demand for high-performance batteries.

[0003] On the one hand, with the urgent need to improve battery energy density, the lightweighting and ultra-thinning of current collectors have become key indicators. After years of attempts, pure copper metal current collectors with a thickness of less than 5 micrometers have not been able to be incorporated into the mass production process and large-scale application of lithium batteries, which to some extent limits the further improvement of battery energy density.

[0004] On the other hand, another key path to improving the energy density of lithium batteries—ultra-high electrode compaction density—poses a significant contradiction with the relatively limited tensile strength of traditional pure copper metal current collectors. If the strength of the current collector cannot be further improved, the continued improvement of battery compaction density will face a major bottleneck.

[0005] Nickel-based materials, due to their high strength and corrosion resistance, possess the fundamental qualities for fabricating high-performance current collectors. However, existing nickel-based composite metal current collectors still face several challenges in their fabrication process. For instance, current collectors prepared through simple physical composite methods exhibit weak interlayer bonding, leading to delamination during subsequent processing and use. While some chemical preparation methods can improve interlayer bonding, they often introduce impurities, affecting the current collector's electrical performance. Furthermore, ensuring structural integrity and performance stability when fabricating ultrathin nickel-based composite metal current collectors (thickness less than 5 μm) remains a pressing technical challenge.

[0006] Ultra-thin nickel foil is considered very difficult to manufacture on a large scale, and the weak conductivity of nickel metal means that it cannot directly meet the overcurrent requirements of battery current collectors. In addition, nickel metal is more expensive than copper foil. Overall, nickel foil has always been considered unsuitable as a material for battery negative electrode current collectors.

[0007] Patent CN118676376A discloses a current collector comprising an iron-nickel alloy substrate and a copper layer disposed on at least one side of the iron-nickel alloy substrate. This patent utilizes a titanium alloy roller to electroplate and deposit the nickel-iron alloy substrate, followed by electroplating and depositing the copper layer on top of it. The current collector obtained by this patent cannot be compressed to a thickness of less than 10 μm, and its tensile strength is 400-800 MPa, presenting a contradiction between its thickness and tensile strength properties.

[0008] In view of the above, this application is hereby submitted. Utility Model Content

[0009] The purpose of this invention is to provide an ultrathin, high-tensile-strength composite metal current collector. By designing the preparation process of the bed, separator, and current collector functional layer, as well as the formulation of the plating solution, the composite current collector is made ultrathin while the tensile strength is significantly improved compared to other current collectors of the same thickness.

[0010] To achieve the above objectives, the present invention adopts the following technical solution: In a first aspect, this utility model provides an ultrathin high tensile strength composite metal current collector, comprising a nickel metal layer and a copper metal layer disposed on both sides or any one side of the nickel metal layer; The nickel metal layer comprises pure nickel.

[0011] Secondly, this utility model also provides a method for preparing an ultrathin high-tensile-strength composite metal current collector, comprising the following steps: A separator layer is plated onto the bed; A first copper metal layer and a nickel metal layer are sequentially plated on the partition layer; or, a first copper metal layer, a nickel metal layer, and a second copper metal layer are sequentially plated on the partition layer. Separating the separator from the first copper metal layer yields the ultrathin high-tensile composite metal current collector.

[0012] Secondly, this utility model also provides an application of the current collector described above or the current collector prepared by the preparation method described above in lithium-ion batteries, solid-state batteries or smart chips.

[0013] Compared with the prior art, the present invention has the following technical effects: compared with pure copper-based current collectors, it significantly improves tensile strength while meeting the requirements of existing batteries; compared with other nickel-based or nickel-iron alloy current collectors, it has stronger conductivity, higher tensile strength and elongation, and lower manufacturing cost.

[0014] This invention involves preparing a separator layer on a specific bed, followed by electroplating using a specially formulated plating solution to create an ultra-thin current collector functional layer with an overall thickness of less than 5 μm. Compared to traditional current collectors, this effectively reduces weight and can increase battery energy density by 15%-20%. Even more surprisingly, the tensile strength of the current collector prepared by this invention is 3-5 times that of lithium-ion battery copper foil of the same thickness on the market, far exceeding expectations. This makes the current collector less prone to deformation and breakage when facing volume changes during battery charging and discharging, increasing cycle life by more than 30%.

[0015] The ultrathin high-tensile composite metal current collector of this invention has good conductivity and stability, which can effectively reduce battery internal resistance, reduce heat generation, and reduce the risk of thermal runaway. At the same time, the corrosion resistance of the ultrathin high-tensile composite metal current collector material itself also improves its service life and safety in the complex environment of the battery.

[0016] The electroplating method used in the overall preparation process of this utility model has simple equipment, is easy to operate, and is easy to mass-produce. Compared with some complex preparation methods such as physical vapor deposition, the cost is reduced by 20-30%. Attached Figure Description

[0017] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the embodiments will be briefly described below. It should be understood that the following drawings only show some embodiments of this application and should not be regarded as a limitation on the scope of this application.

[0018] Figure 1 This is a schematic cross-sectional view of the ultrathin high tensile strength composite metal current collector of this utility model.

[0019] Figure 2 This is a process flow diagram for the preparation of an ultrathin high-tensile composite metal current collector according to the present invention.

[0020] Figure 3 This is a process flow diagram for another ultrathin high tensile strength composite metal current collector according to the present invention.

[0021] Figure 4 This is a photograph of the current collector obtained in Embodiment 1 of this utility model.

[0022] Figure 5 This is a photograph of the current collector obtained in Embodiment 3 of this utility model.

[0023] Figure 6 This is a cross-sectional electron microscope image of the current collector obtained in Embodiment 3 of this utility model.

[0024] Explanation of reference numerals in the attached figures: 1-First copper metal layer; 2-Nickel metal layer; 3-Second copper metal layer. Detailed Implementation

[0025] The embodiments of this utility model will be described in detail below with reference to specific examples. However, those skilled in the art will understand that the following examples are only for illustrating this utility model and should not be considered as limiting the scope of this utility model. Unless otherwise specified in the examples, conventional conditions or conditions recommended by the manufacturer are followed. Reagents or instruments whose manufacturers are not specified are all commercially available products. Proportions not specified are arbitrary ratios and mass ratios.

[0026] The terminology used in the embodiments of this application is for the purpose of describing particular embodiments only and is not intended to be limiting of this application. The singular forms “a,” “the,” and “the” used in the embodiments of this application and the appended claims are also intended to include the plural forms unless the context clearly indicates otherwise.

[0027] The performance testing methods in the following examples and comparative examples are summarized below: 1. Tensile strength test: Test Method 1: The tensile strength of the current collector is tested using a tensile testing machine. First, the current collector to be tested is cut to a length L≥75mm and a width of 15mm. Then, the two ends of the obtained specimen are clamped with the smooth-faced jaws of the tensile testing machine, ensuring that the specimen's axis is aligned with the center line of the machine jaws. The specimen is then pulled at a low speed of 50mm / min, and the load with displacement is recorded until the specimen breaks. The maximum force reached during the test is recorded, and the tensile strength is obtained by dividing the maximum force by the original cross-sectional area of ​​the specimen.

[0028] For ease of comparison, a second test method was used: the tensile strength of the current collector was tested using a tensile testing machine. First, the current collector to be tested was cut to a length L≥75mm and a width of 12.5mm. Then, both ends of the obtained specimen were clamped with the smooth-faced jaws of the tensile testing machine, ensuring that the specimen's axis was aligned with the center line of the machine jaws. The specimen was then pulled at a low speed of 1.15mm / min, and the load with displacement was recorded until the specimen broke. The maximum force reached during the test was recorded, and the tensile strength was obtained by dividing the maximum force by the original cross-sectional area of ​​the specimen.

[0029] 2. Elongation at break test: Test Method 1: The elongation at break of the current collector is tested using a tensile testing machine. First, the current collector to be tested is cut to a length L≥75mm and a width of 15mm. Then, the two ends of the obtained specimen are clamped with the smooth-faced jaws of the tensile testing machine, ensuring that the specimen's axis is aligned with the center line of the machine jaws. Then, it is pulled at a low speed of 50mm / min, and the load with displacement is recorded until the specimen breaks. The maximum displacement reached during the test is the elongation at break of the current collector.

[0030] For ease of comparison, a second test method was used: the elongation at break of the current collector was tested using a tensile testing machine. First, the current collector to be tested was cut to a length L≥75mm and a width of 12.5mm. Then, the two ends of the obtained specimen were clamped with the smooth-faced jaws of the tensile testing machine, ensuring that the specimen's axis was aligned with the center line of the machine's jaws. Then, the specimen was pulled at a low speed of 1.15mm / min, and the load with displacement was recorded until the specimen broke. The maximum displacement reached during the test is the elongation at break of the current collector.

[0031] 3. Thickness test: The thickness of the current collector is measured using a film thickness tester in accordance with standard GB / T36053-2018.

[0032] This utility model provides an ultra-thin high tensile strength composite metal current collector, which includes a nickel metal layer and a copper metal layer disposed on both sides or any one side of the nickel metal layer. The nickel metal layer comprises pure nickel.

[0033] In some preferred embodiments, the copper metal layer comprises pure copper.

[0034] In some preferred embodiments, the nickel metal layer is pure nickel and the copper metal layer is pure copper; the pure nickel or pure copper, which inevitably contains impurities during the preparation process, is also included in this invention.

[0035] Figure 1 This invention illustrates a preferred embodiment of the present invention, wherein the ultrathin high tensile composite metal current collector comprises, from top to bottom, a first copper metal layer 1, a nickel metal layer 2, and a second copper metal layer 3.

[0036] In some embodiments, the thickness of the nickel metal layer is 0.5-5.0 μm, and the thickness of the copper metal layer is 0.3-2.0 μm.

[0037] In some preferred embodiments, the thickness of the nickel metal layer is 2.0-3.5 μm, and the thickness of the copper metal layer is 0.3-1.0 μm.

[0038] Generally speaking, the thickness of the copper metal layer is less than that of the nickel metal layer.

[0039] Generally, the total thickness of the current collector, consisting of the aforementioned nickel metal layer and copper metal layers disposed on both sides or either side of the nickel metal layer, is no greater than 6 μm. In some preferred embodiments, the total thickness is no greater than 5 μm.

[0040] In some embodiments, the tensile strength of the current collector is not less than 500 MPa; in some preferred embodiments, the tensile strength of the current collector is not less than 1000 MPa.

[0041] In some embodiments, the elongation at break of the current collector is not less than 4%; in some preferred embodiments, the elongation at break of the current collector is not less than 8%.

[0042] This utility model provides a method for preparing an ultrathin high-tensile-strength composite metal current collector, comprising the following steps: S1: Plate a separator layer on the bed.

[0043] In some embodiments, the bed comprises one or more combinations of copper foil, aluminum foil, a composite foil of copper and polymer, stainless steel foil, or iron foil.

[0044] In some embodiments, the thickness of the bed is 5-18 μm.

[0045] In some preferred embodiments, the bed layer is de-oxided or impurities before the separator layer is plated. Specifically, this can be done by pickling the bed layer to remove surface oxides, followed by rinsing with deionized water.

[0046] Furthermore, the pickling involves immersing the food in a dilute sulfuric acid solution with a mass concentration of 5-10% for 10-60 seconds.

[0047] In some embodiments, the interlayer is plated by placing the bed as a cathode in an interlayer electroplating solution, controlling the temperature at 40-60°C, the pH value at 11-13, and the current density at 1-5 A / dm³. 2 The electroplating time is 60-120 seconds, during which an alloy interlayer is formed on the surface of the bed.

[0048] In some embodiments, the thickness of the spacer is 10-100 nm.

[0049] In some embodiments, the interlayer plating solution includes at least nickel salt and molybdenum salt.

[0050] In some embodiments, the alloy spacer includes a nickel-molybdenum alloy spacer.

[0051] In some alternative embodiments, the nickel salt includes one or more of nickel sulfate, nickel chloride, or nickel aminosulfonate.

[0052] In some alternative embodiments, the molybdenum salt includes one or more of sodium molybdate, ammonium molybdate, molybdenum trioxide, molybdenum dioxide, molybdenum tetrachloride, molybdenum pentachloride, or molybdenum disulfide.

[0053] In some embodiments, the interlayer electroplating solution also includes one or more of tartrates and chromates.

[0054] The tartrate can be potassium sodium tartrate. The chromium salt can be one of chromium chloride, chromium sulfate, potassium dichromate, chromium trioxide, or chromium nitrate.

[0055] Adding chromium salts in combination with tartrates can reduce the grain size of the nickel-molybdenum alloy in the interlayer from 1.5 μm to below 200 nm, resulting in a finer crystal structure in the coating. After sequentially plating copper, nickel, and copper on the interlayer surface, neither the nickel nor copper plating layers adhere to the interlayer, preventing them from becoming difficult to separate. The addition of chromium salts in combination with tartrates also makes the coating on the interlayer denser, resulting in a superior ultrathin, high-tensile-strength composite metal current collector.

[0056] In some embodiments, the interlayer electroplating solution further includes one or more of pyrophosphate, citrate, polyethylene glycol 8000, and thiourea.

[0057] Furthermore, the pyrophosphate includes one or more of potassium pyrophosphate, sodium pyrophosphate, etc.; the citrate includes one or more of sodium citrate, potassium citrate, or ammonium citrate, etc.

[0058] Further, if the following substances are present in the interlayer electroplating solution, the concentration of the nickel salt is 5-30 g / L, the concentration of the molybdenum salt is 0.01-0.5 g / L, the concentration of the chromium salt in the interlayer electroplating solution is 0.5-5 g / L, the concentration of the tartrate is 2-10 g / L, the concentration of the pyrophosphate is 50-300 g / L, the concentration of the citrate is 50-150 g / L, the concentration of polyethylene glycol 8000 is 0.01-0.5 g / L, and the concentration of the thiourea is 0.01-0.5 g / L.

[0059] S2: A first copper metal layer and a nickel metal layer are sequentially plated on the partition layer, and the process route is as follows: Figure 2 As shown; or, a first copper metal layer, a nickel metal layer, and a second copper metal layer are sequentially plated on the interlayer, with the process route as follows: Figure 3 As shown.

[0060] In some embodiments, the first copper metal layer is plated by placing the product of the plating layer as a cathode in a first electroplating solution, controlling the temperature at 45-60°C, the pH value at 7-10, and the current density at 1-5 A / dm³. 2 The electroplating time is 30-300 seconds, and the first copper metal layer is formed by electroplating on the surface of the interlayer.

[0061] In some embodiments, the thickness of the first copper metal layer is 0.3-2.0 μm; in some preferred embodiments, the thickness of the first copper metal layer is 0.3-1.0 μm.

[0062] In some embodiments, the anode corresponding to the cathode includes one or more of oxygen-free copper, electrolytic copper, or phosphorus copper.

[0063] In some embodiments, the first electroplating solution includes a copper salt, and also includes one or more combinations of pyrophosphate, citrate, or sodium polydithiopropane sulfonate.

[0064] In some alternative embodiments, the copper salt comprises one or more of copper methanesulfonate, copper sulfate, or copper pyrophosphate. The concentration of the copper salt is 30-150 g / L.

[0065] Furthermore, the pyrophosphate includes one or more of potassium pyrophosphate, sodium pyrophosphate, etc.; the citrate includes one or more of sodium citrate, potassium citrate, or ammonium citrate, etc.

[0066] Further, if the following substances are present in the first electroplating solution, the concentration of the pyrophosphate is 50-500 g / L, the concentration of the citrate is 5-50 g / L, and the concentration of the sodium polydisulfide dipropane sulfonate is 2-10 ppm / L.

[0067] In some embodiments, the nickel plating metal layer is formed by placing the product of the first copper plating metal layer as a cathode in a second electroplating solution, controlling the temperature at 45-65°C, the pH value at 2-6, and the current density at 2-50 A / dm³. 2 The electroplating time is 20-500 seconds, and the nickel metal layer is formed on the surface of the first copper metal layer by electroplating.

[0068] In some embodiments, the thickness of the nickel metal layer is 0.5-5.0 μm; in some preferred embodiments, the thickness of the nickel metal layer is 2.0-3.5 μm.

[0069] In some embodiments, the anode corresponding to the cathode includes an electrolytic nickel plate and / or a sulfur-containing nickel cake.

[0070] In some embodiments, the second electroplating solution includes a nickel salt; it also includes one or more of boric acid, sodium vinyl sulfonate, or sodium ethylhexyl sulfate.

[0071] In some alternative embodiments, the nickel salt comprises one or more of nickel aminosulfonate, nickel chloride, or nickel sulfate. The nickel ion concentration of the nickel salt is 30-200 g / L.

[0072] Further, if the following substances are present in the second electroplating solution, the concentration of boric acid is 10-100 g / L, the concentration of sodium vinyl sulfonate is 0.001-0.1 g / L, and the concentration of sodium ethylhexyl sulfate is 0.001-0.1 g / L.

[0073] In some embodiments, the second copper metal layer is plated by placing the product of the nickel metal layer as a cathode in a third electroplating solution, controlling the temperature at 45-60°C, the pH value at 7-10, and the current density at 1-5 A / dm³. 2 The electroplating time is 30-300 seconds, and a second copper metal layer is formed on the surface of the nickel metal layer by electroplating.

[0074] In some embodiments, the thickness of the second copper metal layer is 0.3-2.0 μm; in some preferred embodiments, the thickness of the second copper metal layer is 0.3-1.0 μm.

[0075] In some embodiments, the anode corresponding to the cathode includes one or more of oxygen-free copper, electrolytic copper, or phosphorus copper.

[0076] In some embodiments, the third electroplating solution includes copper salts, and also includes one or more combinations of pyrophosphates, citrates, or sodium polydithiopropane sulfonate.

[0077] In some alternative embodiments, the copper salt comprises one or more of copper methanesulfonate, copper sulfate, or copper pyrophosphate. The concentration of the copper salt is 30-150 g / L.

[0078] Furthermore, the pyrophosphate includes one or more of potassium pyrophosphate, sodium pyrophosphate, etc.; the citrate includes one or more of sodium citrate, potassium citrate, or ammonium citrate, etc.

[0079] Further, if the following substances are present in the third electroplating solution, the concentration of the pyrophosphate is 50-500 g / L, the concentration of the citrate is 5-50 g / L, and the concentration of the sodium polydisulfide dipropane sulfonate is 2-10 ppm / L.

[0080] S3: Separate the partition layer and the first copper metal layer to obtain the ultra-thin high tensile composite metal current collector. The obtained current collector can be cut, inspected, and packaged for storage.

[0081] The separation of the separator and the first copper metal layer can be carried out after high-temperature baking and annealing, which helps to improve the elongation at break to some extent.

[0082] The current collector provided in this embodiment or the current collector prepared by the method described herein can be used in lithium-ion batteries, solid-state batteries or smart chips.

[0083] The present invention will be further described below through specific embodiments.

[0084] Example 1 A method for preparing an ultrathin, high-tensile-strength composite metal current collector: (1) Immerse 10μm lithium battery copper foil in a dilute sulfuric acid solution with a mass concentration of 8% for 30 seconds to remove oxides from the surface of the copper foil, and then clean it with deionized water to serve as a bed layer. (2) Prepare a barrier electroplating solution, including nickel sulfate hexahydrate with a concentration of 10 g / L, potassium pyrophosphate with a concentration of 200 g / L, sodium molybdate dihydrate with a concentration of 0.1 g / L, polyethylene glycol-8000 with a concentration of 0.1 g / L, potassium sodium tartrate with a concentration of 5 g / L, and chromium chloride with a concentration of 3 g / L. Place the resulting bed into the barrier electroplating solution, with the copper foil of the bed as the cathode and the iridium-tantalum alloy titanium mesh as the anode. Control the electroplating temperature at 55°C, the pH value at 11, and the current density at 2 A / dm³. 2 The electroplating time is 120 seconds, and a nickel-molybdenum alloy separator with a thickness of about 50 nm is formed on the surface of the bed. (3) Prepare the first electroplating solution, which includes potassium pyrophosphate at a concentration of 260 g / L, copper pyrophosphate at a concentration of 70 g / L, ammonium citrate at a concentration of 20 g / L, and sodium polydisulfide dipropane sulfonate at a concentration of 5 ppm / L. Use the product of step (2) as the cathode and the oxygen-free copper plate as the anode. Place the product in the first electroplating solution and control the electroplating temperature at 50°C, the pH value at 8.3, and the current density at 2 A / dm³. 2 The electroplating time is 75 seconds, and a pure copper plating layer (i.e., the first copper metal layer) with a thickness of about 500 nm is formed on the surface of the interlayer. (4) Prepare a second electroplating solution, including nickel aminosulfonate (nickel ion concentration 100 g / L) at a concentration of 600 ml / L, nickel chloride hexahydrate at a concentration of 10 g / L, boric acid at a concentration of 40 g / L, sodium vinylsulfonate at a concentration of 0.010 g / L, and sodium ethylhexyl sulfate at a concentration of 0.030 g / L. Use the product of step (3) as the cathode and the electrolytic nickel plate as the anode, and place it in the second electroplating solution. Control the electroplating temperature at 60°C, the pH value at 4.0, and the current density at 5 A / dm³. 2 The electroplating time is 180 seconds, and a pure nickel plating layer (i.e., nickel metal layer) with a thickness of about 3000 nm is formed on the surface of the first copper metal layer. (5) Prepare the third electroplating solution, which includes potassium pyrophosphate at a concentration of 260 g / L, copper pyrophosphate at a concentration of 70 g / L, ammonium citrate at a concentration of 20 g / L, and sodium polydisulfide dipropane sulfonate at a concentration of 5 ppm / L. Use the product of step (4) as the cathode and the oxygen-free copper plate as the anode. Place the product in the third electroplating solution and control the electroplating temperature at 50°C, pH value at 8.3, and current density at 2 A / dm³. 2 The electroplating time is 75 seconds, and a pure copper plating layer (i.e., the second copper metal layer) with a thickness of about 500 nm is formed on the surface of the nickel metal layer. (6) Peel off the prepared ultrathin high-tensile current collector, which includes the first copper metal layer, the nickel metal layer, and the second copper metal layer, from the separator, cut it, and inspect it. Figure 4 As shown, the product is packaged and stored. Performance tests are shown in Table 1.

[0085] Example 2 A method for preparing an ultrathin, high-tensile-strength composite metal current collector: (1) Immerse 18μm lithium battery copper foil in a 5% dilute sulfuric acid solution for 60 seconds to remove oxides from the surface of the copper foil, and then clean it with deionized water to serve as a bed layer. (2) Prepare a barrier electroplating solution, including nickel sulfate hexahydrate with a concentration of 10 g / L, potassium pyrophosphate with a concentration of 200 g / L, sodium molybdate dihydrate with a concentration of 0.1 g / L, polyethylene glycol-8000 with a concentration of 0.1 g / L, potassium sodium tartrate with a concentration of 5 g / L, and chromium sulfate with a concentration of 5 g / L. Place the resulting bed into the barrier electroplating solution, with the copper foil of the bed as the cathode and the iridium-tantalum alloy titanium mesh as the anode. Control the electroplating temperature at 55°C, the pH value at 11, and the current density at 5 A / dm³. 2 The electroplating time is 60 seconds, and a nickel-molybdenum alloy separator with a thickness of about 100nm is formed on the surface of the bed. (3) Prepare the first electroplating solution, which includes potassium pyrophosphate at a concentration of 300 g / L, copper pyrophosphate at a concentration of 80 g / L, ammonium citrate at a concentration of 20 g / L, and sodium polydisulfide dipropane sulfonate at a concentration of 5 ppm / L. Use the product of step (2) as the cathode and the oxygen-free copper plate as the anode. Place the product in the first electroplating solution and control the electroplating temperature at 45°C, the pH value at 8.5, and the current density at 2 A / dm³. 2 The electroplating time is 60 seconds, and a pure copper plating layer (i.e., the first copper metal layer) with a thickness of about 400nm is formed on the surface of the interlayer. (4) Prepare a second electroplating solution, including nickel aminosulfonate (nickel ion concentration 100 g / L) at a concentration of 600 ml / L, nickel chloride hexahydrate at a concentration of 10 g / L, boric acid at a concentration of 40 g / L, sodium vinylsulfonate at a concentration of 0.010 g / L, and sodium ethylhexyl sulfate at a concentration of 0.030 g / L. Use the product of step (3) as the cathode and the electrolytic nickel plate as the anode, and place it in the second electroplating solution. Control the electroplating temperature at 65°C, the pH value at 4.5, and the current density at 7 A / dm³. 2 The electroplating time is 120 seconds, and a pure nickel plating layer (i.e., nickel metal layer) with a thickness of about 3000 nm is formed on the surface of the first copper metal layer. (5) Prepare the third electroplating solution, which includes potassium pyrophosphate at a concentration of 300 g / L, copper pyrophosphate at a concentration of 80 g / L, ammonium citrate at a concentration of 20 g / L, and sodium polydisulfide dipropane sulfonate at a concentration of 5 ppm / L. Use the product of step (4) as the cathode and the oxygen-free copper plate as the anode. Place the product in the third electroplating solution and control the electroplating temperature at 50°C, pH value at 8.5, and current density at 2 A / dm³. 2 The electroplating time is 60 seconds, and a pure copper plating layer (i.e., the second copper metal layer) with a thickness of about 400nm is formed on the surface of the nickel metal layer. (6) The prepared ultrathin high-tensile current collector, consisting of a first copper metal layer, a nickel metal layer, and a second copper metal layer, is peeled off from the separator, cut, inspected, packaged, and stored. Performance tests are shown in Table 1.

[0086] Example 3 A method for preparing an ultrathin, high-tensile-strength composite metal current collector: (1) Immerse 15μm lithium battery copper foil in a 10% dilute sulfuric acid solution for 10 seconds to remove oxides from the surface of the copper foil, and then clean it with deionized water to serve as a bed layer. (2) Prepare a barrier electroplating solution, including nickel sulfate hexahydrate with a concentration of 10 g / L, potassium pyrophosphate with a concentration of 200 g / L, sodium molybdate dihydrate with a concentration of 0.1 g / L, polyethylene glycol-8000 with a concentration of 0.1 g / L, potassium sodium tartrate with a concentration of 5 g / L, and chromium nitrate with a concentration of 4 g / L. Place the resulting bed into the barrier electroplating solution, with the copper foil of the bed as the cathode and the iridium-tantalum alloy titanium mesh as the anode. Control the electroplating temperature at 60℃, the pH value at 12, and the current density at 3 A / dm³. 2 The electroplating time is 80 seconds, and a nickel-molybdenum alloy separator with a thickness of about 80nm is formed on the surface of the bed. (3) Prepare the first electroplating solution, which includes potassium pyrophosphate at a concentration of 300 g / L, copper pyrophosphate at a concentration of 80 g / L, ammonium citrate at a concentration of 20 g / L, and sodium polydisulfide dipropane sulfonate at a concentration of 5 ppm / L. Use the product of step (2) as the cathode and the oxygen-free copper plate as the anode, and place it in the first electroplating solution. Control the electroplating temperature at 60°C, the pH value at 8.0, and the current density at 1 A / dm³. 2 The electroplating time is 150 seconds, and a pure copper plating layer (i.e., the first copper metal layer) with a thickness of about 500 nm is formed on the surface of the interlayer. (4) Prepare a second electroplating solution, including nickel aminosulfonate (nickel ion concentration 100 g / L) at a concentration of 600 ml / L, nickel chloride hexahydrate at a concentration of 10 g / L, boric acid at a concentration of 40 g / L, sodium vinylsulfonate at a concentration of 0.010 g / L, and sodium ethylhexyl sulfate at a concentration of 0.030 g / L. Use the product of step (3) as the cathode and the electrolytic nickel plate as the anode, and place it in the second electroplating solution. Control the electroplating temperature at 50°C, the pH value at 5.0, and the current density at 20 A / dm³. 2 The electroplating time is 35 seconds, and a pure nickel plating layer (i.e., nickel metal layer) with a thickness of about 2500 nm is formed on the surface of the first copper metal layer. (5) Prepare the third electroplating solution, which includes potassium pyrophosphate at a concentration of 300 g / L, copper pyrophosphate at a concentration of 80 g / L, ammonium citrate at a concentration of 20 g / L, and sodium polydisulfide dipropane sulfonate at a concentration of 5 ppm / L. Use the product of step (4) as the cathode and the oxygen-free copper plate as the anode. Place the product in the third electroplating solution and control the electroplating temperature at 60°C, pH value at 8.0, and current density at 3 A / dm³. 2 The electroplating time is 150 seconds, and a pure copper plating layer (i.e., the second copper metal layer) with a thickness of about 500 nm is formed on the surface of the nickel metal layer. (6) Peel off the prepared ultrathin high-tensile current collector, which includes the first copper metal layer, the nickel metal layer, and the second copper metal layer, from the separator, cut it, inspect it, and the product is as follows: Figure 5 As shown, the product is packaged and stored. Simultaneously, the cross-section of the product is characterized using electron microscopy, as shown... Figure 6 As shown in the figure, the remaining performance tests are shown in Table 1.

[0087] Example 4 The difference from Example 1 is that the sodium polydithiopropane sulfonate in steps (3) and (5) was increased from 5 ppm / L to 10 ppm / L. Performance tests are shown in Table 1.

[0088] Example 5 The difference from Example 1 is that the potassium pyrophosphate concentration in steps (3) and (5) was changed from 300 g / L to 250 g / L. Performance tests are shown in Table 1.

[0089] Example 6 The difference from Example 1 is that the boric acid concentration in step (4) was changed from 40 g / L to 30 g / L. Performance tests are shown in Table 1.

[0090] Example 7 The difference from Example 1 is that the concentration of nickel sulfamate (nickel ion concentration 100 g / L) in step (4) was reduced from 600 ml / L to 400 ml / L. Performance tests are shown in Table 1.

[0091] Example 8 The difference from Example 1 is that the concentration of sodium vinyl sulfonate in step (4) was increased from 0.010 g / L to 0.015 g / L. Performance tests are shown in Table 1.

[0092] Example 9 The difference from Example 1 is that chromium chloride is not added to the interlayer electroplating solution in step (2). In actual operation, this will lead to a slight decrease in the strength of the finished product, while increasing the peeling force and peeling difficulty. Performance tests are shown in Table 1.

[0093] Example 10 The difference from Example 1 is that chromium chloride and sodium potassium tartrate were not added to the interlayer electroplating solution in step (2). In the resulting product, the surface of the first copper metal layer in contact with the interlayer showed discoloration, mainly due to uneven interlayer electroplating caused by the lack of sodium potassium tartrate. Performance tests are shown in Table 1.

[0094] Example 11 The difference from Example 1 is that, in step (6), before peeling the prepared ultrathin high-tensile current collector, which includes a first copper metal layer, a nickel metal layer, and a second copper metal layer, from the separator, it is subjected to high-temperature annealing at 150°C for 3 hours. The performance test results are shown in Table 1.

[0095] Comparative Example 1 The difference from Example 1 is that the 5 ppm / L sodium polydisulfide dipropane sulfonate in steps (3) and (5) is replaced with 0 ppm / L. Performance tests are shown in Table 1.

[0096] Comparative Example 2 The only difference from Example 1 is that the concentration of sodium vinyl sulfonate in step (4) was changed from 0.010 g / L to 0 g / L. Performance tests are shown in Table 1.

[0097] Comparative Example 3 The only difference from Example 1 is that the plating bath temperature in step (4) was reduced from 60°C to 40°C. Performance tests are shown in Table 1.

[0098] Comparative Example 4 The difference from Example 1 is that chromium chloride and potassium sodium tartrate were not added to the interlayer electroplating solution in step (2). Performance tests are shown in Table 1.

[0099] Comparative Example 5 (1) Immerse 10μm lithium battery copper foil in a dilute sulfuric acid solution with a mass concentration of 8% for 30 seconds to remove oxides from the surface of the copper foil, and then clean it with deionized water to serve as a bed layer. (2) Prepare a barrier electroplating solution, including nickel sulfate hexahydrate with a concentration of 10 g / L, potassium pyrophosphate with a concentration of 100 g / L, sodium molybdate dihydrate with a concentration of 0.1 g / L, polyethylene glycol-8000 with a concentration of 0.1 g / L, potassium sodium tartrate with a concentration of 5 g / L, and chromium chloride with a concentration of 3 g / L. Place the resulting bed into the barrier electroplating solution, with the copper foil of the bed as the cathode and the iridium-tantalum alloy titanium mesh as the anode. Control the electroplating temperature at 551℃, the pH value at 11, and the current density at 2 A / dm³. 2 The electroplating time is 120 seconds, and a nickel-molybdenum alloy separator with a thickness of about 50 nm is formed on the surface of the bed. (3) Prepare a second electroplating solution, including nickel aminosulfonate (nickel ion concentration 100 g / L) at a concentration of 600 ml / L, nickel chloride hexahydrate at a concentration of 10 g / L, boric acid at a concentration of 40 g / L, sodium vinylsulfonate at a concentration of 0.010 g / L, and sodium ethylhexyl sulfate at a concentration of 0.030 g / L. Use the product of step (2) as the cathode and the electrolytic nickel plate as the anode, and place it in the second electroplating solution. Control the electroplating temperature at 60°C, the pH value at 4.0, and the current density at 5 A / dm³. 2 The electroplating time is 300 seconds, and a pure nickel plating layer (i.e., nickel metal layer) with a thickness of about 4900 nm is formed on the surface of the first copper metal layer. (4) The prepared nickel metal layer current collector is peeled off from the separator, and the performance test results are shown in Table 1.

[0100] Comparative Example 6 is the nickel-iron alloy current collector of Example 1 in Chinese Patent CN118676376A.

[0101] Comparative Examples 7, 8, and 9 are high-tensile copper current collectors with thicknesses of 4.5mm, 5mm, and 6mm respectively from Nord New Materials Co., Ltd.

[0102] Table 1 Comparison of performance test results of current collectors obtained in the examples and comparative examples As can be seen from the test results in Table 1, the overall thickness of the current collectors in Examples 1-11 can be as small as 4 μm or even less, while the tensile strength can reach 1550 MPa, the elongation at break can mostly reach over 9%, and the sheet resistance fully meets the normal requirements for current collectors. It is evident that with extremely small thickness, the tensile strength is exceptionally high, while the conductivity fully meets the usage requirements.

[0103] Compared with Comparative Example 5, the current collectors prepared in Examples 1-11 (except for Example 10, which did not have chromium chloride and potassium sodium tartrate added at the same time) showed an unexpectedly significant improvement in tensile strength. Furthermore, the pure nickel current collector in Comparative Example 5 had a relatively high resistance, which caused the battery to overheat easily during battery applications, posing a certain degree of danger.

[0104] Similarly, compared to Comparative Example 5, Comparative Example 6 exhibits worse properties such as thickness and tensile strength.

[0105] Compared with Comparative Examples 7, 8, and 9, the current collectors prepared in Examples 1-11 have significantly higher tensile strength than traditional high-tensile copper current collectors.

[0106] The above embodiments are only used to illustrate the technical solutions of this utility model, and are not intended to limit it. Although the utility model has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this utility model.

[0107] Furthermore, those skilled in the art will understand that although some embodiments herein include certain features included in other embodiments but not others, combinations of features from different embodiments are meant to be within the scope of this invention and form different embodiments. For example, in the foregoing claims, any of the claimed embodiments can be used in any combination. The information disclosed in this background section is intended only to enhance the understanding of the general background of this invention and should not be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.

Claims

1. An ultrathin high-tensile composite metal current collector, characterized in that, It includes a nickel metal layer and a copper metal layer disposed on both sides or either side of the nickel metal layer; The nickel metal layer comprises pure nickel; The thickness of the nickel metal layer is 0.5-5.0 μm, and the thickness of the copper metal layer is 0.3-2.0 μm.

2. The ultrathin high-tensile composite metal current collector according to claim 1, characterized in that, The thickness of the nickel metal layer is 2.0-3.5 μm, and the thickness of the copper metal layer is 0.3-1.0 μm.

3. The ultrathin high-tensile composite metal current collector according to claim 1, characterized in that, The total thickness of the current collector is no greater than 6 μm.

4. The ultrathin high-tensile composite metal current collector according to claim 3, characterized in that, The total thickness of the current collector is no greater than 5 μm.

5. The ultrathin high-tensile composite metal current collector according to any one of claims 1-4, characterized in that, The thickness of the copper metal layer is less than that of the nickel metal layer.

6. The ultrathin high-tensile composite metal current collector according to claim 1, characterized in that, The tensile strength of the current collector is not less than 500 MPa.

7. The ultrathin high-tensile composite metal current collector according to claim 6, characterized in that, The tensile strength of the current collector is not less than 1000 MPa.

Citation Information

Patent Citations

  • Current collector, negative pole piece, secondary battery and electric device

    CN118676376A